Mannose Promotes β‐Amyloid Pathology by Regulating BACE1 Glycosylation in Alzheimer's Disease - Chensi Liang; Ziqi Yuan; Shangchen Yang; Yufei Zhu; Zhenlei Chen; Dan Can; Aiyu Lei; Huifang Li; Lige Leng; Jie Zhang (Advanced Science)
Abstract Hyperglycemia accelerates Alzheimer's disease (AD) progression, yet the role of monosaccharides remains unclear. Here, it is demonstrated that mannose, a hexose, closely correlates with the pathological characteristics of AD, as confirmed by measuring mannose levels in the brains and serum of AD mice, as well as in the serum of AD patients. AD mice are given mannose by intra‐cerebroventricular injection (ICV) or in drinking water to investigate the effects of mannose on cognition and AD pathological progression. Chronic mannose overload increases β‐amyloid (Aβ) burdens and exacerbates cognitive impairments, which are reversed by a mannose‐free diet or mannose transporter antagonists. Mechanistically, single‐cell RNA sequencing and metabolomics suggested that mannose‐mediated N‐glycosylation of BACE1 and Nicastrin enhances their protein stability, promoting Aβ production. Additionally, reduced mannose intake decreased BACE1 and Nicastrin stability, ultimately lowering Aβ production and mitigating AD pathology. this results highlight that high‐dose mannose consumption may exacerbate AD pathogenesis. Restricting dietary mannose may have therapeutic benefits.